The effect of peer education to anxiety of teenagers in post menarche in sub district Kasihan Bantul, Indonesia - Yati, Dwi; Rachman, Irwan T.; Ikka, Wahyu (International Journal of Research in Medical Sciences, 2017)
Background: Menarche is an important event in puberty of teenagers. The coming of menarche often causes negative reactions and anxiety. Most teenagers get information about menarche from her friend so that the information obtained is not necessarily true and accurate. In order to reduce anxiety it should be given the right information with various methods and media. These raised our interest to determine the effect of peer education on adolescent anxiety post-menarche. Methods: A quasi experimental equivalent pre-post test control group design was used in this study with quantitative and qualitative approaches. Time of data retrieval was August-September 2014. Subject were classified into two groups that were treatment group was located in SMP Muhammadiyah and control group was located in SMP Mataram Kasihan region, district Bantul. The division of the group is done by raffle. Intervention for the treatment group of peer education and booklet. The total sample in this study was 86 adolescents post menarche taken by purposive sampling in accordance with the inclusion and exclusion criteria. The anxiety instrument being used TMAS (Taylor Manifest Anxiety Scale). Analysis data: univariate, bivariate and qualitative analysis to strengthen the result of the study with indepth interview for 5 participants. Statistical test using chi square. Results: The result showed that percentage of respondents who experience anxiety when pre-test 43 (100%) and post-test was 34 (79.1%) versus 3 (7.0%). The result of chi square test with p value 0.000 (p<0.05) means that there was significant differences in anxiety reduction before and after a given peer education. The results of the qualitative analysis among teenagers after attending peer education told that they feeling happy, peer education reduced anxiety, confusion and fear because of peer education increased knowledge, provide an overview and motivation of the problems, means discussion, sharing stories and experiences. Conclusions: Peer education and booklet could reduce anxiety post menarche of teenagers.